PENGARUH TOTAL ASSET TURNOVER (TATO) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA INDUSTRI ASURANSI DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2014 - Ahmadi Ahmadi; Muhammad Alhudhori (Universitas Batanghari Jambi, 2015)
Profitability ratios of one of them is Return on Equity (ROE). Return On Equity (ROE) is a ratio that measures how much profit rightful owners of their own capital. Activities ratio, ie the ratio that measures the efficiency of the company in the use of its assets. Total Asset Turnover (TATO) and Return On Equity (ROE) on stock price is 0.295 or 29.5%. This shows that with the same Total Asset Turnover (TATO) and Return On Equity (ROE) affect stock prices by 29.5% and amounted to 70.5% influenced by other variables not examined in this study. Based on the calculation coefficient of determination can be seen that simultaneously the influence of Total Asset Turnover (TATO) and Return On Equity (ROE) on stock price is 0.295 or 29.5%. The management company should need to improve the company's financial performance for the development of Total Asset Turnover (TATO), Return on Equity (ROE) is likely to decline and thus may affect the stock price decline. For the insurance industry should be trying to improve the company's financial performance in order to increase the stock price so that investors will continue to invest in the companyKeyword: total sset turnover, return on equity Profitability ratios of one of them is Return on Equity (ROE). Return On Equity (ROE) is a ratio that measures how much profit rightful owners of their own capital. Activities ratio, ie the ratio that measures the efficiency of the company in the use of its assets. Total Asset Turnover (TATO) and Return On Equity (ROE) on stock price is 0.295 or 29.5%. This shows that with the same Total Asset Turnover (TATO) and Return On Equity (ROE) affect stock prices by 29.5% and amounted to 70.5% influenced by other variables not examined in this study. Based on the calculation coefficient of determination can be seen that simultaneously the influence of Total Asset Turnover (TATO) and Return On Equity (ROE) on stock price is 0.295 or 29.5%. The management company should need to improve the company's financial performance for the development of Total Asset Turnover (TATO), Return on Equity (ROE) is likely to decline and thus may affect the stock price decline. For the insurance industry should be trying to improve the company's financial performance in order to increase the stock price so that investors will continue to invest in the companyKeyword: total sset turnover, return on equity